2022
DOI: 10.3390/diagnostics12122989
|View full text |Cite
|
Sign up to set email alerts
|

Urine and Saliva: Relevant Specimens for Malaria Diagnosis?

Abstract: Blood remains the specimen of preference for malaria diagnosis, whether it is for microscopic, nucleic acid-based or biomarker detection of Plasmodium present in a patient. However, concerning the disadvantages of blood drawing, specimens that can be non-invasively collected under non-hygienic settings would come in handy for malaria diagnosis in endemic areas with limited resources. Although the current approaches using saliva or urine might not be as sensitive and specific as using blood, the potential of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 65 publications
2
3
0
Order By: Relevance
“…In the present study, we found (Table 2) that the light yellow color of urine, low or normal urine density, the presence of bacteria, the presence of few leukocytes and few lymphocytes in the urine can signal an efficient response to treatment with injectable antimalarials, because these factors appeared to be protective of hospital resistance to antimalarial treatment (P<0.05), but showed the cloudy appearance of urine, high pH, presence of few crystals and presence of other microorganisms in the urine may be signs of resistance to hospital treatment injectable with antimalarial (P>0.05). These data reinforce what was said by Kalantari and collaborators (2015) and Chai & Chua (2022), that urine, as it is an ultrafiltrate of the blood, if it contains the majority of specific plasma or serum proteins and low molecular weight, can be a suitable sample for investigating the pathological process not only of renal diseases, but also of systemic or infectious diseases [21,22].…”
Section: Discussionsupporting
confidence: 85%
“…In the present study, we found (Table 2) that the light yellow color of urine, low or normal urine density, the presence of bacteria, the presence of few leukocytes and few lymphocytes in the urine can signal an efficient response to treatment with injectable antimalarials, because these factors appeared to be protective of hospital resistance to antimalarial treatment (P<0.05), but showed the cloudy appearance of urine, high pH, presence of few crystals and presence of other microorganisms in the urine may be signs of resistance to hospital treatment injectable with antimalarial (P>0.05). These data reinforce what was said by Kalantari and collaborators (2015) and Chai & Chua (2022), that urine, as it is an ultrafiltrate of the blood, if it contains the majority of specific plasma or serum proteins and low molecular weight, can be a suitable sample for investigating the pathological process not only of renal diseases, but also of systemic or infectious diseases [21,22].…”
Section: Discussionsupporting
confidence: 85%
“…In the present study, we found (Table 2) that the light yellow color of urine, low or normal urine density, the presence of bacteria, the presence of few leukocytes and few lymphocytes in the urine can signal an efficient response to treatment with injectable antimalarials, because these factors appeared to be protective of hospital resistance to antimalarial treatment (P<0.05), but showed the cloudy appearance of urine, high pH, presence of few crystals and presence of other microorganisms in the urine may be signs of resistance to hospital treatment injectable with antimalarial (P>0.05). These data reinforce what was said by Kalantari and collaborators (2015) and Chai & Chua (2022), that urine, as it is an ultrafiltrate of the blood, if it contains the majority of specific plasma or serum proteins and low molecular weight, can be a suitable sample for investigating the pathological process not only of renal diseases, but also of systemic or infectious diseases [21,22].…”
Section: Discussionsupporting
confidence: 85%
“…Some biomarkers in biofluid samples only exist at very dilute protein content levels (e.g., those in urine or saliva). 108 Therefore, digital-based approaches have been introduced to help the quantitative analytical analysis, such as in the limit of detection. Yang et al 100 developed a droplet-based optofluidic platform to quantify specific individual EV subpopulations, and in a high throughput manner.…”
Section: Extracellular Vesicle Characterizationmentioning
confidence: 99%